SALIVARY PARAMETERS, ORAL HEALTH HABITS, AND SOCIOECONOMIC ASPECTS AS RISK FACTORS FOR DENTAL CARIES IN 12-YEAR-OLD CHILDREN FROM A PRIVATE SCHOOL OF THE CITY OF CURITIBA, BRAZIL - Azevedo, Luiza Foltran; Arruda, Eduardo Silva; Brancher, João Armando; dos Santos, Thatiani Bandeira; Ignácio, Sérgio Aparecido; Pecharki, Giovana Daniela; Faucz, Fábio Rueda; Moysés, Simone Tetu; Batista, Paulo Sérgio; Trevilatto, Paula Cristina (Archives of Oral Research, 2005)
OBJECTIVES: The aim of this study was to compare socioeconomic aspects, oral health habits and salivary parameters between 12-year-old students with and without caries experience. MATERIAL AND METHODS: A sample of 113 non-related 12-year-old subjects was selected in a private school of Curitiba-PR, Brazil, for a case-control study. They were divided into groups with and without caries experience through the DMFT index. The frequency of tooth brushing, use of dental floss, diet, frequency of dentist visit, fluoride use, dental plaque index, socioeconomic aspects and salivary parameters were evaluated. Data were analyzed by qui-square and Mann-Whitney. RESULTS: Results showed no statistical difference between the groups in relation to oral hygiene habits and socioeconomic status. It was observed an association between dental plaque presence and caries experience, although not significant (p = 0.08). A reduced salivary flow was highly associated with decay experience (p = 0.00). CONCLUSION: It was concluded that the salivary flow was an important factor to determine dental caries experience in a homogeneous group of children from a private school of Curitiba-PR. Studies on host response aspects may be desirable in this kind of populations.